Android Smartphone Among Young People - Setiadi, Daryono; Rahayuningsih, Nurjanah; Surianti, Surianti; Anwar, Samsul (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine purchasing decisions among young people who need their daily life is still filled by the lord yes. Android smartphones among young people are still included in the category of expensive items. The sample used is young people who are still learning and have no income. Consumers in determining the decision to purchase products are influenced by including price perceptions, product features, and word of mouth. Consumer complaints about price perceptions are caused by Android smartphones perceived to be more expensive. Price perception is related to how price information is understood entirely by consumers and gives a deep meaning to them, three indicators namely: Price conformity to product quality, Price conformity to benefits and Competitive prices. Product features are elements of a product that are considered important by consumers and are used as the basis for making a purchasing decision, researchers use four indicators, namely: Diversity of Features, Quality of Features, Importance of Features and Completeness of Features. Word of Mouth or WOM is the act of providing any information related to the product by consumers to other consumers. there are three indicators of Word of Mouth, namely: Word of Mouth Organic, Word of Mouth Amplified and Word of Mouth Marketing. The purchase decision is a decision as the choice of an action of two or more alternative choices, there are six indicators namely: Product choice, Brand choice, Time choice, Store choice, Choice of amount and Choice of payment. From the results of this study it was found that the influence of Price Perception (X‚), Product Features (X‚‚) and Word of Mouth (X‚ƒ) on Purchasing Decisions (Y) had a very strong and positive effect because when young people whose financial needs were still met from his parents or young people who have not worked is largely determined by the variable Price Perception (X ‚), Product Features (X ‚‚) and Word of Mouth (X ‚ƒ) together or simultaneously affect the Purchase Decision (Y) of an android smartphone.